Big vision, small business : - Walters, Jamie S. (Ivy Sea Publishing, 2001)
While most of the business world glorifies growth, Big Vision, Small Business celebrates the art — and power — of thinking small. Based on more than 70 interviews with small-business owners and on the author’s own experience as a small-business entrepreneur, this book demonstrates that a company doesn’t have to be big to make a significant impact. According to the author, a new kind of business owner is emerging. Defining business success qualitatively as well as quantitatively, these individuals ensure that their bottom line balances personal priorities and social responsibilities. Named the Best Book of the Year by The CEO Refresher, an online business newsletter, Big Vision, Small Business discusses four areas integral to big-vision, small-business ownership: engaging in inspired planning, knowing which model of growth to follow, maintaining successful employee and customer relationships, and seeking balance and integrity.